Alkali-free glass substrate
By adjusting the composition of the glass substrate and spraying SO2 gas to form a sodium sulfate protective film, the problems of scratches and reduced TFT reliability during the manufacturing process are solved, and high-quality and high-productivity alkali-free glass substrates are achieved. Meets the requirements of high strain point and acid resistance.
Patent Information
- Application Number
- CN202211424319.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-09
- Filing Date
- 2019-03-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2039-03-08
AI Technical Summary
The existing alkali-free glass substrates are prone to scratches during the manufacturing process, and the reliability of TFTs is reduced, and the productivity is not high. Especially when the high strain point and acid resistance requirements are increased, it is difficult to take into account the characteristics and molten properties of the glass substrate.
By adjusting the composition of the glass, the strain point of the glass substrate is above 650°C, and the average thermal expansion coefficient of 50 to 350°C is within the range of 30×10 to 7 to 45×10 to 7/°C, and contains 54 to 66% SiO2. 10-25% Al2O3, 0.1-12% B2O3, and SO2 gas is sprayed on the surface to form a sodium sulfate protective film to reduce scratches and inhibit the diffusion of Na2O. The amount of Na2O on the surface of at least one glass substrate is 20 less than the internal amount. Quality or above ppm.
The manufacturing of high-quality alkali-free glass substrates is achieved, reducing scratches and reduced reliability of TFTs, while improving productivity, meeting the requirements of high strain point and acid resistance.
Smart Images

Figure CN115611510B_ABST
Abstract
Description
[0001] This application is a divisional application filed for an application with a filing date of March 8, 2019, an application number of 201980017599.0, and an invention name of “Alkali-free Glass Substrate”. Technical Field
[0002] The present invention relates to a glass substrate suitable for forming a thin film transistor (TFT) or the like. Background Art
[0003] As various glass substrates for displays, especially when thin films such as TFT are formed on glass substrates, borosilicate glass substrates containing almost no alkali metal components (so-called alkali-free glass substrates) can be used. If a glass substrate containing a large amount of alkali metal components is used, the alkali metal components in the glass deteriorate the film properties, resulting in a decrease in the reliability of the TFT. In addition, the glass substrate for displays is also required to have a high strain point and high acid resistance.
[0004] Alkali-free glass with high strain point and excellent acid resistance requires glass raw materials to be melted at a high temperature of 1400-1800°C, and it is not easy to efficiently produce high-quality glass substrates. Patent Document 1 describes a method in which alkali-free glass contains 200-2000 ppm of alkali metal oxides and the glass is melted by heating with a burner flame and heating by passing electricity through the molten glass.
[0005] The float process is known as a method for forming glass into a plate. In the float process, molten glass is formed into a plate by flowing on molten metal (eg, molten tin) continuously supplied to a float bath (hereinafter sometimes simply referred to as a "bath").
[0006] The glass ribbon formed on the molten metal is then conveyed using rollers. At this time, it is known that the portion in contact with the rollers is easily scratched.
[0007] As a method for preventing such scratches, it is known that sulfurous acid gas (SO2 gas) is sprayed on the back of a glass substrate to react with an alkali metal (such as sodium) present in the glass to form sodium sulfate on the back of the glass substrate, which acts as a protective film (for example, Patent Document 2). In addition, Patent Document 3 describes a method of spraying sodium tetraborate or the like on the surface of a display panel glass and then spraying sulfurous acid gas.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2013 / 084832
[0011] Patent Document 2: International Publication No. 2002 / 051767
[0012] Patent document 3: International Publication No. 2008 / 004480. Summary of the invention
[0013] However, the method described in Patent Document 2 cannot be applied to the production of alkali-free glass substrates in which the amount of alkali metals present in the glass is extremely small. In addition, the method described in Patent Document 3 can also be applied to alkali-free glass substrates, but since two kinds of gases are blown on the surface of the glass ribbon, the process is complicated and the device also becomes complicated.
[0014] Furthermore, recently, requirements for TFT characteristics and glass substrate characteristics have further increased, and it has become more difficult to achieve both maintaining the characteristics of the TFT on the glass substrate and improving the solubility of the glass.
[0015] The present invention has been made in view of the above problems, and an object of the present invention is to provide a high-quality alkali-free glass substrate having less reduction in reliability of TFTs based on alkali metal components, less scratches, and excellent productivity.
[0016] After repeated research, the inventors found that the above-mentioned problems can be solved by a glass substrate having a strain point and an average thermal expansion coefficient of 50 to 350° C. within a specified range, a specific composition, and an amount of Na2O on the surface of at least one glass substrate being less than the amount of Na2O inside the glass substrate by 20 mass ppm or more, thereby completing the present invention.
[0017] That is, the present invention relates to an alkali-free glass substrate having a strain point of 650°C or higher and an average thermal expansion coefficient of 30×10 -7 ~45×10 -7 / ℃, expressed as mass % based on oxides, contains 54-66% SiO2, 10-25% Al2O3, 0.1-12% B2O3, a total of 7-25% of one or more components selected from MgO, CaO, SrO and BaO, contains 150-2000 mass ppm Na2O, and the amount of Na2O on the surface of at least one main surface of the glass substrate is more than 20 mass ppm less than the amount of Na2O inside the glass substrate.
[0018] The alkali-free glass substrate of the present invention has a specific composition, and the amount of Na2O on the surface of at least one glass substrate is less than the amount of Na2O inside the glass substrate by 20 mass ppm or more, thereby reducing the scratches on the surface of the glass substrate and suppressing the reliability reduction of the TFT based on the alkali metal component. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It indicates the thickness direction of the glass substrate.23 Na + and 30 Si + A diagram of an example of a signal intensity ratio distribution.
[0020] Figure 2 This is a diagram showing an example of Na2O content distribution near the surface of a glass substrate.
[0021] Figure 3 This is a conceptual diagram showing a glass manufacturing apparatus based on the float process.
[0022] Figure 4 This is an example of the relationship between the change in threshold voltage in a reliability test of a TFT formed on the surface of a glass substrate and the amount of Na2O on the surface of the glass substrate.
[0023] Figure 5 It is a schematic diagram showing a TFT element. DETAILED DESCRIPTION
[0024] Hereinafter, the mode for implementing the present invention will be described in detail. However, the present invention is not limited to the embodiment described below.
[0025] In the present specification, the glass composition is expressed in principle as mass % based on oxides, and "%" and "ppm" used in the present specification for the glass composition mean "mass %" and "mass ppm" unless otherwise specified.
[0026] In this specification, "alkali-free glass" refers to glass in which the content of alkali metal components such as lithium, sodium, and potassium is 5000 ppm or less in terms of oxide.
[0027] In this specification, the "glass ribbon" refers to molten glass formed into a plate shape. The glass ribbon is cooled, cut, etc. to form a glass substrate.
[0028] The "bottom surface" is the surface in contact with the molten metal in the float bath of the glass ribbon or glass substrate produced by the float process. The "top surface" is the surface opposite to the bottom surface.
[0029] In this specification, the Na2O content of a glass substrate is obtained by powdering the glass substrate, decomposing the obtained glass powder by heating with sulfuric acid, nitric acid and hydrofluoric acid, and concentrating it until white sulfuric acid smoke is generated to obtain a constant volume solution dissolved in dilute nitric acid, and quantifying the Na concentration in the constant volume solution by ICP mass spectrometry [unit: mass ppm].
[0030] The "Na2O content inside the glass substrate" is equal to the Na2O content of the glass substrate obtained by the above method.
[0031] The "Na2O content on the surface of the glass substrate" was determined as follows: a portion of the glass substrate to be evaluated was cut out and etched about 10 μm (specifically 8 to 12 μm) from the surface using a 5% aqueous hydrogen fluoride solution, and the sample was used as a standard sample, and the C 60 The Na content distribution was obtained by the sputtering time-of-flight secondary ion mass spectrometry (TOF-SIMS) method, and the Na content was determined from the distribution.
[0032] Specifically, the average Na2O content in a region having a depth of 0.25 μm to 0.30 μm from the surface, which was obtained from the Na content distribution of the glass, was defined as the Na2O content on the surface of the glass substrate.
[0033] Figure 1 The thickness direction of the glass substrate is obtained by the following steps 23 Na + and 30 Si + Signal intensity ratio distribution diagram.
[0034] That is, five small pieces were cut out from the glass substrate, and the surface of four of them was etched using a 5% aqueous solution of hydrogen fluoride. By changing the etching time for the five small pieces, 1 μm, 3 μm, 5 μm, and 10 μm were etched from the surface of the glass substrate, respectively. The etching thickness was measured using a micrometer.
[0035] For each small piece, use C 60 Sputtering time-of-flight secondary ion mass spectrometry (TOF-SIMS) 23 Na + and 30 Si + The signal intensity ratio of Figure 1 As shown. Si is the main component of the glass substrate, and its content is roughly the same in the thickness direction of the glass substrate. 23 Na + and 30 Si + The signal intensity ratio can be regarded as representing the distribution of Na content.
[0036] according to Figure 1 It is found that the Na content is lower in a region up to a depth of about 5 μm from the glass substrate surface than in a deeper portion, but the Na content does not change at a depth of about 10 μm or more.
[0037] As a method for determining the Na2O content on the surface of a glass substrate, the following method can be cited, that is, a portion of the glass substrate to be evaluated is cut out, and about 10 μm (specifically 8 to 12 μm) from the surface is etched using a 5% hydrogen fluoride aqueous solution, and as a standard sample for quantifying Na2O, the Na2O content of the unetched glass substrate is measured relative to the sputtering time.23 Na + and 30 Si + The Na content distribution near the surface of the glass substrate was determined by measuring the signal intensity ratio of
[0038] At depths above about 10 μm, the Na content does not change, so the Na content is 23 Na + and 30 Si + The signal intensity ratio of is equivalent to the Na2O content determined by the IPC mass spectrometry. Therefore, the signal intensity ratio can be converted to the Na2O content using this value. After the TOF-SIMS measurement, a surface shape measuring device (e.g., Dektak150 manufactured by Veeco) is used to measure the Na2O content using C 60 When measuring the depth of sputtering grinding, convert the sputtering time into the depth from the glass surface.
[0039] Thus, we get Figure 2 The Na2O content distribution is shown. The average Na2O amount in the region from 0.25 μm to 0.30 μm deep from the surface of the Na2O content distribution thus obtained was taken as the Na2O amount on the glass surface.
[0040] In this specification, the "β-OH value" of a glass substrate is obtained by the following method.
[0041] That is, the infrared transmittance of the glass substrate was measured using an infrared spectrophotometer, and the wave number was 3500 to 3700 cm -1 The minimum value of the transmittance is set to I a [Unit: %], wave number 4000cm -1 The transmittance is set to I b [Unit: %], when the thickness of the glass substrate is d [unit: mm], the β-OH value is -(log(I a / I b )) / d[Unit: mm -1 ].
[0042] [Method for manufacturing glass substrate]
[0043] First, to facilitate understanding of the present invention, a method for manufacturing a glass substrate based on a float process is described as one method for manufacturing an alkali-free glass substrate of the present invention (hereinafter also referred to as “the glass substrate of the present invention”), but the method for manufacturing the glass substrate of the present invention is not limited thereto.
[0044] Float-based glass substrate manufacturing includes:
[0045] (I) a "melting step" of melting raw materials to produce molten glass;
[0046] (II) a "forming step" of introducing molten glass into a float bath to form a glass ribbon; and
[0047] (III) A "slow cooling step" of slowly cooling the glass ribbon using a slow cooling furnace.
[0048] Hereinafter, a conceptual diagram showing an example of a glass manufacturing apparatus based on the float process will be used. Figure 3 Each process is described.
[0049] <Melting process>
[0050] In the melting step, glass raw materials prepared and mixed according to a desired glass composition are put into a melting furnace 3 to obtain molten glass 4. The temperature of the melting furnace 3 may be appropriately adjusted according to the glass raw materials used, and is, for example, about 1400°C to 1600°C.
[0051] <Molding process>
[0052] In the forming step, molten glass 4 is continuously poured from a melting furnace 3 onto a molten tin surface of a float bath 2 that meets molten tin 1, thereby forming a glass ribbon.
[0053] The glass ribbon formed on the molten metal is preferably conveyed to the slow cooling furnace 6 by the conveying rollers 5 and slowly cooled, and SO 2 gas is sprayed on the bottom surface of the glass ribbon between the time when the glass ribbon comes out of the float bath 2 and when it contacts the conveying rollers 5 .
[0054] By spraying the SO2 gas, Na2O present on the glass surface reacts with the SO2 gas to form sodium sulfate on the glass surface. The sodium sulfate has the effect of preventing the glass ribbon from being scratched due to contact between the glass ribbon and the conveying roller 5, and can be easily removed by washing with water, so it does not affect the quality of the glass substrate.
[0055] Therefore, in the manufacturing process of the glass substrate of the present invention, which is an alkali-free glass substrate with a low Na2O content, in order to form sodium sulfate on the glass surface in an amount sufficient to prevent scratches on the glass substrate, for example, by appropriately adjusting the water vapor concentration in the float tank, the temperatures on the upstream and downstream sides of the float tank 2, the residence time of the molten glass 4, the dissolved oxygen concentration in the molten tin 1, etc., the Na2O inside the glass moves to the vicinity of the bottom surface and is unevenly distributed, and by blowing SO2 gas, sodium sulfate can be sufficiently generated on the glass surface, thereby obtaining a glass substrate with few scratches.
[0056] Furthermore, by moving Na2O in the glass to the vicinity of the bottom surface and distributing it unevenly, the amount of Na2O diffused from the glass surface to the molten tin can be increased, and the amount of Na2O contained in the entire glass substrate can be reduced.
[0057] Specific conditions for the temperatures on the upstream and downstream sides of the float bath 2 , the residence time of the molten glass 4 , and the dissolved oxygen concentration in the molten tin 1 include, for example, the following (1) to (4).
[0058] (1) The temperature on the upstream side of the float bath 2 is preferably 1400 to 900° C., more preferably 1300 to 1000° C., and further preferably 1250 to 1100° C. The temperature on the upstream side of the float bath 2 indicates the temperature of the upstream glass ribbon and can be measured using a radiation thermometer.
[0059] (2) The temperature on the downstream side of the float bath 2 is preferably 600 to 850° C., more preferably 650 to 850° C., and further preferably 700 to 800° C. The temperature on the downstream side of the float bath 2 indicates the temperature of the glass ribbon downstream and can be measured using a radiation thermometer.
[0060] (3) The residence time of the molten glass 4 is preferably 5 to 60 minutes, more preferably 10 to 40 minutes, and still more preferably 15 to 30 minutes.
[0061] (4) The dissolved oxygen concentration in the molten tin 1 is preferably 10 ppm or less, more preferably 5 ppm or less, further preferably 3 ppm or less, and most preferably 0 ppm. The dissolved oxygen concentration in the molten tin 1 can be measured using a tin oxygen concentration meter (Redox).
[0062] By blowing SO2 gas, Na2O concentrated near the bottom surface of the glass substrate is converted into sodium sulfate and dispersed to the outside of the glass substrate. Therefore, the amount of Na2O on the glass surface of the bottom surface side of the glass substrate obtained by the above method is less than the amount of Na2O inside the glass, specifically, less by 20 mass ppm or more, preferably less by 40 mass ppm or more, and more preferably less by 90 mass ppm or more.
[0063] It should be noted that the temperature of the heat treatment during the manufacture of TFTs is generally 400°C to 500°C, but the temperature of the glass ribbon during the spraying of SO2 gas is about 600°C to 750°C, which is higher than the temperature of the heat treatment during the manufacture of TFTs. Therefore, by spraying SO2 gas, Na ions existing at a deeper position than the depth of Na ion diffusion in the glass substrate during the heat treatment during the manufacture of TFTs can be reacted with SO2 and removed.
[0064] Therefore, when a TFT is manufactured using the glass substrate obtained by the above method, diffusion of Na ions in the glass into the TFT during heat treatment is small, and changes in threshold voltage can be suppressed, thereby manufacturing a TFT with excellent reliability.
[0065] <Slow cooling process>
[0066] In the slow cooling step, the glass ribbon conveyed by the conveying rollers 5 can be slowly cooled in the slow cooling furnace 6 to obtain the glass substrate of the present invention. The temperature of the slow cooling furnace 6 is not particularly limited, and can be set to 550-750° C. on the upstream side of the slow cooling furnace 6 and 200-300° C. on the downstream side, similar to the conditions of a general float process.
[0067] [Glass composition]
[0068] Next, the glass composition of the glass substrate of the present invention will be described.
[0069] The glass substrate of the present invention contains, expressed in terms of mass % based on oxides, 54 to 66% of SiO2, 10 to 25% of Al2O3, 0.1 to 12% of B2O3, a total of 7 to 25% of one or more components selected from MgO, CaO, SrO and BaO, and 150 to 2000 mass ppm of Na2O, wherein the amount of Na2O on at least one glass surface is less than 20 mass ppm or more of Na2O inside the glass.
[0070] Hereinafter, each component will be described in detail.
[0071] <SiO2>
[0072] SiO2 is an essential component of alkali-free glass.
[0073] When the content of SiO2 in the glass substrate of the present invention is small, the strain point is low, the thermal expansion coefficient is large, and the density is large. Therefore, the content of SiO2 in the glass substrate of the present invention is 54% or more, preferably 57% or more, and more preferably 58% or more.
[0074] On the other hand, when the content of SiO2 is high, the viscosity of the glass is high, and the viscosity of the glass becomes 10 2 dPa·s temperature T2, becomes 10 4 The temperature T4 of dPa·s increases, and the devitrification temperature increases. Therefore, the content of SiO2 in the glass substrate of the present invention is 66% or less, preferably 63% or less, and more preferably 62% or less.
[0075] <Al2O3>
[0076] When the content of Al2O3 in the glass substrate of the present invention is small, the glass phase separation occurs and the strain point decreases. Therefore, the content of Al2O3 in the glass substrate of the present invention is 10% or more, preferably 14% or more, and more preferably 15% or more.
[0077] On the other hand, when the content of Al2O3 is too high, the glass viscosity becomes 10 2 dPa·s temperature T2, becomes 10 4The temperature T4 of dPa·s increases, and the devitrification temperature may increase. Therefore, the Al2O3 content of the glass substrate of the present invention is 25% or less, preferably 21% or less, and more preferably 18% or less.
[0078] <B2O3>
[0079] When the content of B2O3 in the glass substrate of the present invention is small, the viscosity of the glass becomes high and the devitrification temperature increases. However, the content of B2O3 in the glass substrate of the present invention is 0.1% or more, preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. In addition, from the viewpoint of preventing fogging by etching using buffered hydrofluoric acid, it is preferably 3% or more, and more preferably 5% or more.
[0080] On the other hand, when the content of B2O3 is too much, the strain point decreases. Therefore, the content of B2O3 in the glass substrate of the present invention is 12% or less, preferably 11% or less, and more preferably 9% or less. In addition, when it is particularly desired to increase the strain point, it is preferably 7% or less, more preferably 5% or less, and further preferably 3% or less.
[0081] <MgO, CaO, SrO and BaO>
[0082] In the glass substrate of the present invention, MgO, CaO, SrO and BaO are not essential, and these components have the effect of reducing the viscosity of the glass and maintaining chemical durability. Therefore, the total content of these components in the glass substrate of the present invention is 7% or more, preferably 9% or more, and more preferably 12% or more.
[0083] On the other hand, when these components are contained in excess, the thermal expansion coefficient of the glass becomes too large. Therefore, the total content of these components in the glass substrate of the present invention is 25% or less, preferably 21% or less, and more preferably 18% or less.
[0084] MgO is a component that has the least effect of increasing the thermal expansion coefficient of glass among alkaline earth oxides. In addition, it is also a component that can increase the Young's modulus while maintaining the density of glass at a low level. The content of MgO is preferably 1% or more, more preferably 2% or more, and further preferably 3% or more. On the other hand, the devitrification temperature is lowered by reducing the content of MgO, so the content of MgO is preferably 10% or less, more preferably 8% or less, and further preferably 6% or less.
[0085] CaO is a component that can increase Young's modulus without increasing the thermal expansion coefficient and density. The content of CaO is preferably 2% or more, more preferably 3% or more. On the other hand, if the CaO content is reduced, the glass is less likely to lose clarity. Therefore, the content of CaO is preferably 15% or less, more preferably 10% or less, and further preferably 6% or less.
[0086] SrO has the effect of reducing the viscosity without raising the devitrification temperature of the glass, and is preferably contained in an amount of 6% or more. On the other hand, the thermal expansion coefficient can be reduced by reducing the content of SrO, so the content of SrO is preferably 15% or less, more preferably 10% or less, and further preferably 9% or less.
[0087] BaO is a component that reduces viscosity. Since the thermal expansion coefficient can be reduced by reducing the content of BaO, the content of BaO is preferably 5% or less, more preferably 1% or less. Moreover, in the case where the density is to be reduced for the purpose of lightening the glass substrate, it is preferably 0.5% or less, and more preferably substantially not contained.
[0088] <Na2O>
[0089] Generally, when a TFT is formed on a glass substrate, a heat treatment is performed afterwards. However, when the glass contains a large amount of Na2O, Na ions in the glass diffuse into the TFT during the heat treatment, and the threshold voltage of the TFT changes, thereby reducing the reliability of the TFT. Therefore, the Na2O content in the glass substrate of the present invention is 2000 mass ppm or less, preferably 1000 mass ppm or less, and more preferably 800 mass ppm or less.
[0090] On the other hand, when the Na2O content of the glass is too low, the melting characteristics of the glass deteriorate. Therefore, the Na2O content in the glass substrate of the present invention is 150 mass ppm or more, preferably 300 mass ppm or more, and more preferably 500 mass ppm or more.
[0091] As described above, the glass substrate of the present invention can reduce scratches on the surface of the glass substrate by making the amount of Na2O on the surface of at least one main surface of the glass substrate 20 mass ppm or more less than the amount of Na2O inside the glass substrate.
[0092] Therefore, the amount of Na2O on the surface of at least one main surface of the glass substrate of the present invention is 20 mass ppm or more less than the amount of Na2O inside the glass substrate, preferably 40 mass ppm or more less, and more preferably 90 mass ppm or more less.
[0093] In the glass substrate of the present invention, by setting the Na2O content within the above range, the reliability of the TFT formed on the glass substrate is prevented from decreasing. However, the reliability of the TFT is particularly affected by the Na2O present on the surface of the glass substrate. Therefore, in the glass substrate of the present invention, by making the amount of Na2O on the surface of the glass substrate of at least one main surface smaller than the amount of Na2O inside the glass substrate, the reliability of the TFT can be further suppressed.
[0094] The reliability of TFT can be evaluated by, for example, a BT test (bias temperature stress test). Figure 4 The graph shows the relationship between the change in threshold voltage and the Na2O content on the surface of a glass substrate when a low-temperature polysilicon thin-film transistor (LTPS-TFT) is formed on the bottom side surface of a glass substrate and a BT test is performed by applying a forward bias.
[0095] Here, the LTPS-TFT structure is a standard top-gate coplanar structure, and the source and drain regions are formed by ion implantation of boron to form a p-channel TFT. The polysilicon film is formed by irradiating an amorphous silicon film with a thickness of 50nm obtained by plasma CVD with XeCl excimer laser (wavelength 308nm) to crystallize it.
[0096] In addition, a 100nm thick silicon oxide film is formed between the glass substrate and the silicon film as a barrier film. LTPS-TFT is processed at a higher temperature than the amorphous silicon TFT that is currently the mainstream, so it has the characteristic of being more strongly affected by the Na2O content on the surface of the glass substrate.
[0097] like Figure 4 It can be seen that the smaller the Na2O content on the surface of the glass substrate, the smaller the change in threshold voltage, that is, the higher the reliability of the TFT. In addition, it can be seen that the smaller the Na2O content on the surface of the glass substrate, the more significant this feature is.
[0098] Therefore, in the glass substrate of the present invention, the amount of Na2O on the surface of the glass substrate of at least one main surface is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and further preferably 250 mass ppm or less.
[0099] <Other ingredients>
[0100] The glass substrate of the present invention is an alkali-free glass, but it is known that alkali metal oxides are inevitably mixed in as impurities in glass raw materials. Generally, Na2O accounts for most of the alkali metal oxides mixed in as impurities from the raw materials, and sometimes Li2O and K2O are contained. When these are contained, the total amount of alkali metal oxides including Na2O is 5000 mass ppm or less, preferably 2000 mass ppm or less, more preferably 1000 mass ppm or less, and further preferably 800 mass ppm or less.
[0101] Furthermore, the glass substrate of the present invention may contain F, Cl, SO 3 , SnO 2 , ZrO 2 , and the like within a range that exhibits the effects of the present invention.
[0102] [Physical properties of glass substrate]
[0103] Next, the physical properties of the glass substrate of the present invention will be described.
[0104] The glass substrate of the present invention has a strain point of 650°C or higher and an average thermal expansion coefficient of 30×10 -7 ~45×10 -7 / ℃.
[0105] <Strain Point>
[0106] In the glass substrate of the present invention, when the strain point is low, when the glass substrate is exposed to high temperature in the thin film forming process of the display, etc., shrinkage (thermal shrinkage) accompanied by deformation of the glass substrate and stabilization of the structure of the glass is likely to occur. Therefore, the strain point of the glass substrate of the present invention is 650°C or more, preferably 660°C or more, and more preferably 670°C or more.
[0107] On the other hand, if the strain point is low, the temperature of the molding device can be reduced, so there is also an advantage that the life of the molding device can be improved. The strain point is preferably not too high. Therefore, the strain point of the glass substrate of the present invention is preferably 800°C or less, more preferably 750°C or less, and further preferably 730°C or less.
[0108] In addition, the strain point is measured by the fiber drawing method based on the method specified in JIS R3103-2 (2001).
[0109] <Average thermal expansion coefficient at 50 to 350°C>
[0110] Since the glass substrate has excellent thermal shock resistance and excellent productivity in TFT panel manufacturing, the average thermal expansion coefficient of the glass substrate of the present invention at 50 to 350°C is 30×10 -7 ~45×10 -7 The average thermal expansion coefficient of the glass substrate of the present invention at 50 to 350°C is preferably 33×10 -7 / °C or more, more preferably 35×10 -7 / °C or more. And preferably 42×10 -7 / °C or less, more preferably 40×10 -7 / ℃ below.
[0111] In addition, the average thermal expansion coefficient is measured using a thermal dilatometer according to the method specified in ASTM E831.
[0112] <Density>
[0113] The density of the glass substrate of the present invention is not particularly limited, but is preferably 3.0 g / cm from the viewpoint of achieving lightweight products and improving the specific elastic modulus. 3 More preferably, it is 2.8 g / cm3 Below, more preferably 2.6 g / cm 3 the following.
[0114] <Viscosity becomes 10 2 Poise (dPa·s) Temperature T2>
[0115] In addition, the viscosity η of the glass substrate of the present invention is 10 2 The lower the poise (dPa·s) temperature T2, the easier it is to melt. From the viewpoint of solubility, the temperature T2 is preferably 1800°C or lower, more preferably 1750°C or lower, further preferably 1700°C or lower, and particularly preferably 1680°C or lower.
[0116] <Viscosity η becomes 10 4 Temperature T4 of poise (dPa·s)
[0117] The viscosity η of the glass substrate of the present invention is 10 4 The poise (dPa·s) temperature T4 is relatively low and is suitable for float molding. From the viewpoint of float moldability, the temperature T4 is preferably 1350° C. or lower, more preferably 1325° C. or lower, further preferably 1300° C. or lower, and particularly preferably 1290° C. or lower.
[0118] The temperature T2 and the temperature T4 were measured using a rotational viscometer according to the method specified in ASTM C965-96.
[0119] <Young's modulus>
[0120] The Young's modulus of the glass substrate of the present invention is 70 GPa or more, and more preferably 75 GPa or more. The Young's modulus is measured by an ultrasonic pulse method according to the method specified in JIS Z2280 (1993).
[0121] <Photoelastic constant>
[0122] The photoelastic constant of the glass substrate of the present invention is preferably 33 nm / MPa / cm or less.
[0123] Due to stress generated during the manufacturing process of a liquid crystal display panel or when a liquid crystal display device is used, the glass substrate has birefringence, and black display may turn gray, thereby reducing the contrast of the liquid crystal display.
[0124] The photoelastic constant is preferably 33 nm / MPa / cm or less because this phenomenon can be suppressed to a small extent. The photoelastic constant is more preferably 32 nm / MPa / cm or less, and further preferably 30 nm / MPa / cm or less.
[0125] The photoelastic constant of the glass substrate of the present invention is preferably 21 nm / MPa / cm or more, and more preferably 23 nm / MPa / cm or more, in consideration of the ease of securing other physical properties. The photoelastic constant is measured by a disk compression method at a measurement wavelength of 546 nm.
[0126] <Relative dielectric constant>
[0127] When the glass substrate of the present invention is applied to an embedded touch panel (a touch sensor is built into a liquid crystal display panel), the relative dielectric constant of the glass substrate is preferably high from the viewpoint of improving the sensing sensitivity of the touch sensor, reducing the driving voltage, and saving power.
[0128] Therefore, the relative dielectric constant of the glass substrate of the present invention is preferably 5.0 or more, more preferably 5.5 or more, and further preferably 5.7 or more. The relative dielectric constant can be measured by the method described in JIS C-2141 (1992).
[0129] <β-OH value>
[0130] The β-OH value of the glass substrate of the present invention can be appropriately selected based on the required properties of the glass substrate. From the viewpoint of increasing the strain point of the glass substrate, a low β-OH value is preferred. Specifically, the β-OH value is preferably 0.50 mm -1 Below, more preferably 0.45mm -1 Below, more preferably 0.40 mm -1 the following.
[0131] The β-OH value can be adjusted according to various conditions during the melting of the raw materials, such as the amount of water in the glass raw materials, the water vapor concentration in the melting furnace, the residence time of the molten glass in the melting furnace, and the like.
[0132] [Method for manufacturing TFT]
[0133] Next, in order to facilitate understanding of the present invention, a method for manufacturing the TFT element 10 using a glass substrate is described below. Figure 5 An example of a method for manufacturing a top-gate coplanar LTPS-TFT will be described, but the application of the glass substrate of the present invention is not limited to this.
[0134] If necessary, first, a barrier film 12 is formed on one main surface of the glass substrate 11. The barrier film 12 is made of, for example, silicon oxide, silicon oxynitride, silicon carbide, or aluminum oxide, but may be omitted. Next, an amorphous silicon layer as a semiconductor is formed on the barrier film 12 (or the glass substrate 11).
[0135] Next, if the hydrogen concentration in the amorphous silicon layer is reduced by performing a heat treatment, film peeling in subsequent processes can be prevented. The heat treatment is performed, for example, at a temperature of 450 to 600° C. Next, the amorphous silicon is crystallized by laser annealing to obtain a polycrystalline silicon layer 13. Laser annealing is performed, for example, by irradiating an excimer laser with a wavelength of 308 nm. Thereafter, the polycrystalline silicon layer 13 is formed into a predetermined shape. The pattern is performed, for example, by photolithography and etching. Next, an insulating film and a conductive film are formed. The insulating film is composed of, for example, silicon oxide, silicon oxynitride, silicon nitride, and aluminum oxide, and then a gate insulating film 14a is formed. The thickness of the insulating film is, for example, 30 to 600 nm. In addition, the conductive film is composed of, for example, metals including chromium, molybdenum, aluminum, copper, silver, or alloys thereof, and then patterned to form a gate electrode 15. The thickness of the conductive film is, for example, 30 to 600 nm.
[0136] After the gate electrode 15 is formed, a resistance reduction treatment (resistance reduction treatment) is performed on the portion of the gate electrode 15 protruding from the polysilicon layer 13. The resistance reduction treatment is performed by, for example, ion implantation of B (boron) ions into the polysilicon layer 13. In addition, the implanted ions are activated by heat treatment. The heat treatment may be performed at, for example, 450 to 600° C. for 10 to 60 minutes.
[0137] Next, an interlayer insulating film 14 b is formed. The interlayer insulating film 14 b is made of, for example, silicon oxide, silicon oxynitride, silicon nitride, or aluminum oxide. The interlayer insulating film 14 b is patterned so that a portion of the protruding portion of the polysilicon layer 13 is exposed on both sides of the gate electrode 15 .
[0138] Next, the source electrode 16 and the drain electrode 17 are formed. These electrodes are formed by, for example, depositing a conductive film made of a metal such as chromium, molybdenum, aluminum, copper, silver, or an alloy containing these and then patterning the film.
[0139] Next, a passivation film 18 is formed so as to cover them. The passivation film 18 is made of, for example, silicon oxide, silicon oxynitride, silicon nitride, or aluminum oxide, and has a thickness of, for example, 30 to 600 nm.
[0140] The TFT element 10 can be manufactured in the above manner.
[0141] [Application of glass substrate]
[0142] The use of the glass substrate of the present invention is not particularly limited, but the glass substrate is useful as a glass substrate for displays such as liquid crystal display devices, and the like.
[0143] Example
[0144] Hereinafter, the effects of the present invention will be described in more detail by giving examples of the present invention, but the present invention is not limited to these examples.
[0145] Glass raw materials were melted and formed by float process to obtain glass substrates of Examples 1 to 5. In these examples, SO2 gas was sprayed on the bottom surface of the glass ribbon from the time the glass ribbon came out of the float bath to the time it came into contact with the conveying rollers in the float process.
[0146] The composition of the obtained glass substrate is expressed as mass % based on oxides and is shown in Table 1. It should be noted that Example 1 was produced under conventional production conditions, Examples 2 and 3 were produced by slightly increasing the water vapor concentration in the float tank, and Examples 4 and 5 were produced by further increasing the water vapor concentration in the float tank.
[0147] It should be noted that, in the glass substrate obtained by the float method, the composition of SiO2, Al2O3, B2O3, MgO, CaO, SrO and BaO hardly changes during the glass melting process, so the content of these components is determined based on the blending amount of the glass raw materials.
[0148] Regarding the amount of Na2O inside the glass substrate, the obtained glass substrate was powdered, and the obtained glass powder was decomposed by heating with sulfuric acid, nitric acid and hydrofluoric acid, and then concentrated to produce white sulfuric acid smoke to obtain a constant volume solution dissolved in dilute sulfuric acid. The Na concentration in the constant volume solution was quantified by ICP mass analysis to obtain [unit: mass ppm].
[0149] For the amount of Na2O on the glass substrate surface, use C 60 The amount of Na2O on the bottom surface of the glass substrate was measured by the sputtering TOF-SIMS method using the above-mentioned method. The measurement conditions were as follows.
[0150] Measurement device: TOF.SIMS5 manufactured by ION-TOF
[0151] Primary ion type: Bi +
[0152] Accelerating voltage of primary ions: 25 kV
[0153] Current value of primary ion: 1pA (at 10kHz)
[0154] Grating size of primary ions: 20×20μm 2
[0155] Primary ion bunching: Yes
[0156] Sputtering ion species: C 60 ++
[0157] Acceleration voltage of sputtering ions: 10kV
[0158] Sputtering ion current value: 1.1nA (at 10kHz)
[0159] The grating size of sputtered ions: 100×100μm 2
[0160] Sputtering mode: non-interlaced mode
[0161] Vacuum degree: 5.0×10 -6 mbar
[0162] Table 1 shows the results of measuring β-OH value, density, Young's modulus, average thermal expansion coefficient at 50 to 350° C., T2, T4, glass transition temperature, strain point, photoelastic constant, and relative dielectric constant for the glass substrates of Examples 1 to 5.
[0163] [Table 1]
[0164] Table 1
[0165] Example 1 Example 2 Example 3 Example 4 Example 5 <![CDATA[SiO2]]> 60.0 61.5 61.5 60.0 60.0 <![CDATA[Al2O3]]> 16.7 20.0 20.0 16.7 16.7 <![CDATA[E2O3]]> 8.0 1.4 1.4 8.0 8.0 MgO 3.4 4.7 4.7 3.4 3.4 CaO 4.0 5.4 5.4 4.0 4.0 SrO 7.6 6.8 6.8 7.6 7.6 BaO 0.1 0.1 0.1 0.1 0.1 <![CDATA[Internal Na2O [ppm]]]> 162 756 162 783 648 <![CDATA[Surface Na2O [ppm]]]> 149 736 134 681 397 <![CDATA[Na2O concentration difference [ppm]]]> 13 20 28 102 251 β-OH[ / mm] 0.3 0.24 0.24 0.3 0.3 <![CDATA[Density [g / cm 3 > 2.51 2.58 2.58 2.51 2.51 Young's modulus [GPa] 77 85 85 77 77 <![CDATA[Average coefficient of thermal expansion α 50-350 [×10 -7 / ℃]]]> 38 39 39 38 38 <![CDATA[T2[℃]]]> 1645 1650 1650 1645 1645 <![CDATA[T4[℃]]]> 1275 1295 1295 1275 1275 Glass transition temperature[℃] 715 780 780 715 715 Strain point[℃] 670 715 715 670 670 Photoelastic constant [nm / MPa / cm] 31 27 27 31 31 Relative dielectric constant 5.6 6.1 6.1 5.6 5.6
[0166] (Evaluation of Scratch Ease)
[0167] It is believed that the Na2O on the surface of the glass substrate and the SO in the atmosphere x The reaction generates sulfate, which becomes a buffer lubricant to prevent scratches. The amount of sulfate on the surface of the glass substrate is measured to evaluate the scratching susceptibility. It is believed that the greater the amount of sulfate, the higher the effect of inhibiting scratches. The amount of sulfate on the surface of the glass substrate can be measured by S measurement using fluorescent X-rays.
[0168] The S content was measured using a fluorescent X-ray analyzer (manufacturer: Rigaku, model: ZSX-PrimusII) under the following conditions: Target Rh tube voltage: 50 KV, tube current: 60 mV, optical conditions: attenuator 1 / 1, slit S4, spectroscopic crystal Ge, detector: PC.
[0169] A calibration curve was prepared using several standard samples, and the sulfate content of each sample was measured using the calibration curve. The structure of the S content measurement of each sample is shown in Table 2 below.
[0170] [Table 2]
[0171] Table 2
[0172] S quantity Example 1 1.2kcps Example 2 1.6kcps Example 3 2.4kcps Example 4 6.2kcps Example 5 11.2kcps
[0173] Next, the scratch susceptibility of each sample was evaluated using a friction and wear tester (manufacturer: Shinto Scientific Co., Ltd., model: TYPE40 (high temperature specification)).
[0174] Measuring temperature: 600℃
[0175] Scratch indenter: Silicon nitride pin (front end radius 25 microns)
[0176] Load condition: 10g
[0177] Press head moving speed: 30mm / min
[0178] The results of the evaluation of the scratching susceptibility of each sample showed that severe scratching occurred in Example 1, but no scratching occurred in Examples 2 to 5. In Example 1, the amount of sulfate generated was small, so the sample was easily scratched.
[0179] That is, the glass substrate of Example 1, in which the difference between the amount of Na2O on the surface of the glass substrate and the amount of Na2O inside the glass substrate is less than 20, has insufficient generation of sodium sulfate on the bottom surface of the glass substrate, and is therefore easily scratched, resulting in problems in quality control.
[0180] The glass substrates of Examples 2 and 3 have sodium sulfate generated on the bottom surface, so they are not easily scratched. The glass substrates of Examples 4 and 5 have a large amount of sodium sulfate generated on the bottom surface, so they are even less likely to be scratched.
[0181] In addition, the amount of Na2O on the surface of any glass substrate in Examples 2 to 5 is small enough, so it is believed that the degradation of TFT characteristics when a TFT is formed on the bottom surface is small. The glass substrates in Examples 3 and 5 have particularly small amounts of Na2O on the surface, so it is believed that the degradation of TFT characteristics is particularly small.
[0182] The present invention is described in detail with reference to specific embodiments, and it is obvious to those skilled in the art that various changes and modifications can be made without departing from the purpose and scope of the present invention. This application is based on Japanese patent application (Special Application 2018-043493) filed on March 9, 2018, and its contents are incorporated herein by reference.
[0183] 100...Float glass manufacturing equipment
[0184] 1...Molten tin
[0185] 2...Float tank
[0186] 3...Furnace
[0187] 4...Molten glass
[0188] 5...Transport roller
[0189] 6...Slow cooling furnace
[0190] 10...TFT components
[0191] 11...Glass substrate
[0192] 12...Barrier film
[0193] 13...Polysilicon layer
[0194] 14...Insulation layer
[0195] 14a...Gate insulating film
[0196] 14b...Interlayer insulation film
[0197] 15...Gate electrode
[0198] 16...Source electrode
[0199] 17...Drain electrode
[0200] 18...Passivation film
Claims
1. An alkali-free glass substrate having a strain point of 650°C or higher and an average thermal expansion coefficient of 30×10 -7 ~45×10 -7 / ℃, Young's modulus is above 70GPa, Expressed as mass % based on oxides, it contains 54 to 66% of SiO2, 16.7 to 25% of Al2O3, 0.1 to 5% of B2O3, 2 to 8% of MgO, 2 to 10% of CaO, 6.8% or less of SrO, and a total of 7 to 25% of one or more components selected from MgO, CaO, SrO and BaO, β-OH value is 0.24mm -1 the following, Contains 150-2000 mass ppm of Na2O, The amount of Na2O on the surface of at least one main surface of the glass substrate is less than the amount of Na2O in the interior of the glass substrate by 20 mass ppm or more, The amount of Na2O on the glass surface of at least one main surface is 500 mass ppm or less.
2. The alkali-free glass substrate according to claim 1, wherein The amount of Na2O inside the glass substrate is 300 mass ppm or more.
3. The alkali-free glass substrate according to claim 1 or 2, wherein The viscosity of glass becomes 10 4 The temperature T4 of dPa·s is 1350° C. or less.
4. The alkali-free glass substrate according to claim 1 or 2, wherein The viscosity of glass becomes 10 2 The temperature T2 of dPa·s is 1800° C. or less. The alkali-free glass substrate according to claim 1 or 2, which is obtained by a float process.
6. The alkali-free glass substrate according to claim 5, wherein The one main surface is a bottom surface.
Citation Information
Patent Citations
Inkjet recording device and control method of the same
JP2018043493A
Plate glass with protective film and method of manufacturing the plate glass
WO2002051767A1
Process for producing alkali-free glass substrate
WO2008004480A1
Method for manufacturing alkali-free glass
WO2013084832A1
Chemically toughenable or toughened glass and method of making same
DE102014116798A1